2006
DOI: 10.4103/0019-5545.31577
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain metabolism in schizophrenia: An FDG-PET study

Abstract: Background:Recent technological advances have established beyond any doubt the biological nature of schizophrenia. Functional neuroimaging using FDG-PET forms an important technique in understanding the biological underpinnings of psychopathology of schizophrenia.Methods:Eighteen male patients diagnosed as having schizophrenia and having active psychosis as determined by PANSS were subjected to FDG-PET scanning under resting conditions. The glucose uptake in selected regions of interest was studied across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…An increase in relative regional glucose metabolism in the putamen and pallidum in the MAP group when compared to the MAA group was shown in this study, and is in line with work by Seethalakshmi et al (2006) , who showed increased glucose metabolism in the basal ganglia in individuals with active psychosis in schizophrenia. These results therefore seem to be specific to the psychotic group and include regions that are increasingly present in recent work on schizophrenia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An increase in relative regional glucose metabolism in the putamen and pallidum in the MAP group when compared to the MAA group was shown in this study, and is in line with work by Seethalakshmi et al (2006) , who showed increased glucose metabolism in the basal ganglia in individuals with active psychosis in schizophrenia. These results therefore seem to be specific to the psychotic group and include regions that are increasingly present in recent work on schizophrenia.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the considerable diversity of symptoms in schizophrenia, it is widely accepted that impairments are not localized to specific regions, but rather involve the disruption of several regions. Studies looking at active psychosis in Alzheimer's disease and schizophrenia showed decreased cerebral glucose metabolism in the orbitofrontal cortex (OFC) ( Koppel et al, 2014 ), and increases in medial temporal regions, basal ganglia, and left thalamic regions, with decreases in the cerebellum ( Seethalakshmi et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose uptake patterns are reflective of neuronal functioning. Studies[ 20 21 ] have established that individuals with schizophrenia demonstrate specific patterns that can vary with symptoms profiles and chronicity of illness, in other words, the phenomenology of the illness affects glucose uptake. Similarly, studies have observed changes in the orbitofrontal cortex, putamen, and precuneus[ 22 ] and cerebellum[ 23 ] in chronic cannabis users.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that significant heterogeneity in the patterns of schizophrenia make investigations of its origin and mechanisms a major challenge [218]. For example, one study in unmedicated patients showed enhanced glucose metabolism in cerebral white matter, specifically in the frontal white matter, corpus callosum, superior longitudinal fasciculus and white matter core of the temporal lobe.…”
Section: Schizophreniamentioning
confidence: 99%